2018
DOI: 10.1186/s12884-017-1652-6
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous prematurity in fetuses with congenital diaphragmatic hernia: a retrospective cohort study about prenatal predictive factors

Abstract: BackgroundTo evaluate possible predictive factors of spontaneous prematurity in fetuses with congenital diaphragmatic hernia (CDH).MethodsA retrospective cohort study was performed. Inclusion criteria were presence of CDH; absence of fetoscopy; absence of karyotype abnormality; maximum of one major malformation associated with diaphragmatic hernia; ultrasound monitoring at the Obstetrics Clinic of Clinicas Hospital at the University of São Paulo School of Medicine, from January 2001 to October 2014. The data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…A possible reason for the increased risk for prematurity is that fetuses diagnosed with congenital diaphragmatic hernia may be delivered earlier by elective cesarean delivery. A study in Brazil found decreased observed-to-expected lung to head ratio, a variable that we could not measure in our study, a predictor for increased spontaneous prematurity (Barbosa et al, 2018). Since we found survival rates to be lower in LBW/VLBW infants, irrespective of gestational age, it may suggest a greater role for birth weight rather than gestational age in the prognosis of infants with congenital diaphragmatic hernia.…”
Section: Discussioncontrasting
confidence: 68%
“…A possible reason for the increased risk for prematurity is that fetuses diagnosed with congenital diaphragmatic hernia may be delivered earlier by elective cesarean delivery. A study in Brazil found decreased observed-to-expected lung to head ratio, a variable that we could not measure in our study, a predictor for increased spontaneous prematurity (Barbosa et al, 2018). Since we found survival rates to be lower in LBW/VLBW infants, irrespective of gestational age, it may suggest a greater role for birth weight rather than gestational age in the prognosis of infants with congenital diaphragmatic hernia.…”
Section: Discussioncontrasting
confidence: 68%
“…When expectant management is chosen, maternal follow up is comparable to those of uncomplicated pregnancies. Given the increased occurrence of polyhydramnios (more than 30% by the third trimester 39 ), ultrasound scans are usually performed on a monthly basis. In cases with polyhydramnios and shortening of the cervix ultrasound-guided drainage of the excessive amniotic fluid may be RUSSO ET AL.…”
Section: What Are My Options Now?mentioning
confidence: 99%
“…A total of 25,602 records were analyzed, of which 14 corresponded to CDH. The gender involvement was 71.43% male (10 cases) and 28.57% female (4), with 21.34% of Bochdalek-type CDH located on the right (3) and 78.57% on the left (11). All newborns in this study underwent invasive mechanical ventilation (IMV) 9.21 ± 5.55 days.…”
mentioning
confidence: 93%
“…This disorder has postnatal consequences, such as pulmonary hypoplasia and pulmonary hypertension, in addition to abnormal pulmonary vasculature morphology. CDH culminates in indicators of high morbidity and mortality around 50-60%, and individuals with this condition require intensive specialized care 3,4 .…”
Section: Introductionmentioning
confidence: 99%